PENGUKURAN TINGKAT PENYERAPAN BUNYI KEPINGAN BATANG KELAPA SAWIT DENGAN MENGGUNAKAN TABUNG IMPEDANSI - Septina Sari; Erwin '; Krisman ' (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
Research on measuring of levels of sound absorption by a piece of palm trunk wasdone. Sample of palm trunk used in this study was 22 years old and made intorectangular pieces with a size of 23 x 23 cm. The thickness of the samples was varied,namely 6mm, 9mm, 15mm. The source of sound used was generated from sweepfunction generator. The sound intensity inside the impedance tube before and afterpenetrating the sample was recorded using sound level meter. The sound frequencyrange used in this research was 100 Hz - 1000 Hz. The results indicated that in general,the sound intensity increases with the increase of sound frequency. However, theintensity of the sound was reduced very significantly after penetrating the sample insidethe tube. For high frequency, namely 1000 Hz then the percentage of sound absorbtionby a piece of trunk palm with the thickness of 6 mm, 9 mm and 15 mm was 3.4 %, 5.7% and 14 % respectively, while, for low frequency, namely 100 Hz, then the percentageof sound absorbtion by the material with the thickness of 6 mm, 9 mm and 15 mm was5.6 %, 8.3 % and 12 % respectively